Lapis Struktur Fisik dan Batin Pupuh ke-14 Babad Diponegoro (Analisis Strukturalisme Levi Strauss) - Arista Nur Rizki; Muhammad Abdullah (Manuskripta, 2021)
This article is an analysis of the text based from the Sinom’s song in the 14th chapter of the Babad Diponegoro. The Sinom’s song is a traditional song that originated from Java, if this song is categorized in the literary genre, this song is classified as bound poetry. This research aims to describe Prince Diponegoro’s story when he was in his teens. At that time, he was educated by his great-grandmother (wife of Sri Sultan Hamengkubuwono I) in the residence of Tegalrejo, in Yogyakarta. That event tells of a young Prince Diponegoro when he was received education from his great-grandmother, before leading the Java war. The influence of the Tegalrejo village community which has a religious nature and simple lifestyle helped Prince Diponegoro shape his character. The analysis of the text used qualitative methods, with Levis-Strauss’ theory of structuralism. The results can show how the deep structure and surface structure in the Sinom’s song in the 14th chapter of the Babad Diponegoro. === Artikel ini merupakan sebuah analisis terhadap teks berupa tembang Sinom pada pupuh ke-14 Babad Diponegoro. Wujud teks tembang yang berasal dari Jawa ini jika dikategorikan dalam genre sastra merupakan sebuah puisi terikat. Tujuan penelitian ini adalah menjabarkan kisah Pangeran Diponegoro saat menginjak usia remaja, yaitu ketika ia diasuh oleh nenek buyutnya di Tegalrejo, Yogyakarta. Peristiwa ini merupakan wujud proses bagaimana Pangeran Diponegoro mendapatkan pendidikan dari nenek buyutnya sebelum menjadi pemimpin Perang Jawa. Pengaruh masyarakat Tegalrejo yang memiliki sifat religius dengan nuansa pesantren serta adanya pola kesederhanaan turut membentuk karakter Pangeran Diponegoro. Analisis teks ini dilakukan dengan metode kualitatif menggunakan teori strukturalisme Levi-Strauss. Hasil analisis ini menampilkan struktur fisik maupun struktur batin yang terdapat pada tembang Sinom pupuh ke-14 Babad Diponegoro.